ChemInform Abstract: Copper‐Catalyzed C—O Coupling of Styrenes with N‐Hydroxyphthalimide Through Dihydroxylamination Reactions. Issue 6 (21st January 2016) - Xia, Xiao‐Feng; Zhu, Su‐Li; Zhang, Danting
Abstract: The title reaction is successfully performed starting from electron‐neutral or electron‐deficient styrene derivatives, but fails using cyclohexene or norbornene or styrenes with electron‐donating substituents.